Legal Problems in the Implementation of Prior Consultation in Peru: or the "Legal Excuses" of the Government to Violate it - Ruiz Molleda, Juan Carlos (2014)
The objective of this article is to review and analyze the different arguments and legal excuses made by the Government and the private sector in Peru, this for the purpose of that the first-mentioned institution fails or avoids its juridical obligation of execute the preview consultation process for the indigenous peoples in Peru, this whenever the State is going to adopt a legislative or administrative measure susceptible that will affect directly to the indigenous peoples. In summary, this article seeks to analyze about the juridical problems founded at the moment of the implementation of the preview consultation process in our Legal System. If we consider that Convention 169 ILO, and the right to consult has been in force since February 2nd of 1995, and the Constitutional Court established on binding jurisprudence that the Convention in question is a norm that no needs a legislative development for its effectiveness, thus we can conclude that, rather than arguments is about legal excuses.